Relationship between Sputum Eosinophilia and Sinus Disease in Patients with Eosinophilic Bronchitis. Issue 5 (September 2014) - Neighbour, Helen; Goodwin, Jodi; Strychowsky, Julie; Rahman, Sadaf; Abdelshaheed, Rami; Nair, Parameswaran; Sommer, Doron D.
Background: Sinus disease is commonly seen in patients with asthma, and several studies have been published describing the relationship between sinus disease and the inflammation seen in the sputum of asthmatic subjects. In this article, we expand on this knowledge by studying patients with eosinophilic bronchitis with and without asthma. Methods: We describe the relationship between the severity of sinus disease determined by the Lund-Mackay score and sputum eosinophilia. Comparisons with blood eosinophil and total immunoglobulin (IgE) measurements are made. Results: We have shown that the severity of sinus disease is positively correlated with sputum eosinophil counts, and the site of sinus disease affected the level of eosinophilia. There was a positive correlation between sputum eosinophils and blood eosinophils, but there was no relationship with blood total IgE levels. Conclusions: We have confirmed that there is a link between upper and lower airway inflammation and that this is not limited to patients with asthma. The process is associated with systemic inflammation as evidenced by increased blood eosinophils but appears to be independent of IgE.